2015
DOI: 10.1159/000442449
|View full text |Cite
|
Sign up to set email alerts
|

Screening for <b><i>Helicobacter pylori</i></b> in Idiopathic Pulmonary Fibrosis Lung Biopsies

Abstract: Background: Increasing evidence suggests a role of gastro-oesophageal reflux (GER) in idiopathic pulmonary fibrosis (IPF) pathogenesis. Recently, an association between serum Helicobacter pylori (HP) antibody positivity and more severe disease was described, but HP has not been directly analysed in lung tissue so far. Objective: To investigate the presence of HP in the lung tissue of IPF patients. Methods: Two tertiary interstitial lung disease care centre databases were screened for available lung biopsy mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Abnormally prolonged TLESRs create an enlarged hypotensive area at the esophagogastric junction, which results in an increased reflux of gastric contents and gas. Patients with IPF have a hiatal hernia that may impair the structure and function of LES [10, 20, 21, 22, 27, 29, 35, 38], and are characterized with lower LES pressure and upper esophageal sphincter pressure, esophageal peristalsis, and more proximal and distal acid reflux, as compared with healthy controls [10, 30, 33, 34]. Other studies have shown that LES pressure and esophageal peristalsis are preserved in patients with IPF, indicating that TLESR, rather than defective LES, may mainly contribute to GER in IPF [28].…”
Section: The Impact Of Gerd On Ipfmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormally prolonged TLESRs create an enlarged hypotensive area at the esophagogastric junction, which results in an increased reflux of gastric contents and gas. Patients with IPF have a hiatal hernia that may impair the structure and function of LES [10, 20, 21, 22, 27, 29, 35, 38], and are characterized with lower LES pressure and upper esophageal sphincter pressure, esophageal peristalsis, and more proximal and distal acid reflux, as compared with healthy controls [10, 30, 33, 34]. Other studies have shown that LES pressure and esophageal peristalsis are preserved in patients with IPF, indicating that TLESR, rather than defective LES, may mainly contribute to GER in IPF [28].…”
Section: The Impact Of Gerd On Ipfmentioning
confidence: 99%
“…In vitro studies have revealed that bile acids, pepsin, and Hp VacA endotoxin may induce cytotoxic and inflammatory responses or epithelial-mesenchymal transition in lung epithelial cells or fibroproliferative responses in lung fibroblasts [48-50]. Controversially, however, Hp appears to be insignificantly present in the lungs of patients with IPF, as demonstrated by the analysis of DNA, histopathology of lung biopsies, and serological detection of Hp antibody [9, 38, 51]. The potential cellular and molecular mechanisms involving microaspiration in IPF are outlined in Figure 2.…”
Section: The Impact Of Gerd On Ipfmentioning
confidence: 99%
“…While there are many potential explanations for the findings of Kreuter et al [10] that have little to do with the relationship of gastroesophageal reflux-induced microaspiration and IPF (e.g. perhaps there was no microaspiration occurring at the time of biopsy, or there was no H. pylori in the microaspirate at the time of biopsy), it is worth using this interesting study as a cautionary chapter in the ongoing story of gastroesophageal reflux and IPF.…”
mentioning
confidence: 93%
“…In this issue of Respiration , Kreuter et al [10] apply an interesting approach in order to shed more light on the relationship between gastroesophageal reflux, in particular nonacid reflux, and IPF. Their approach was original; they investigated whether H. pylori -containing microaspiration could be involved in IPF pathogenesis by performing PCR screening for H. pylori DNA in lung biopsy specimens of IPF patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation